A Study on Housing Preferences of Residents in Hyderabad Twin Cities - Nahar, Khushi (Journal of Social Science and Humanities, 2025)
This study in Hyderabad, India, examines housing preferences amid population growth and rapid urbanization in the Twin Cities. Using a comprehensive approach involving structured questionnaires and data analysis, the research aims to identify key determinants such as location, amenities, affordability, and lifestyle considerations shaping housing choices. It will explore factors like proximity to workplaces, transportation, safety, and recreational facilities and analyze the impact of cultural, social, and economic factors on diverse demographic groups. The report provides valuable insights for urban planners and real estate developers, guiding the development of tailored housing solutions. Ultimately, the research aims to deepen our understanding of housing market dynamics, inform urban development strategies, and empower residents to make well-informed decisions for an enhanced quality of life in the Twin Cities of Hyderabad.